Translation Studies Today: Old Problems and New Challenges (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article presents a review of the key trends in modern Translation Studies (TS) made after thorough analysis of the most fundamental works written in various fields of TS. The review proves that not only the range of problems within TS is now more diversified, which is related to many changes in the nature of translation activity, but Translation Studies are an interdisciplinary science now and uses data from neighboring disciplines. Specific “turns” have occurred in Translation Studies, and new paradigms of translation investigation have emerged. The most important phenomena in Translation Studies include “cultural turn” and the so called “anthropocentric turn” that has given birth to communicative-functional approach to translation. This approach implies “plunging” into the communicative situation of translation, and its analysis aimed at realizing the goal of translation by the translator/interpreter. It allows a more precise formulation of tasks solved by translators in both traditional types of translation (literary translation, religious translation, interpreting) and relatively new kinds of translation activity (audiovisual translation, localization). The article proves that translation proper is the main element of any activity performed by translators while any translation activity implies cultural adaptation of the text to the perception of the source text audience. The principal feature of Translation Studies is being practice-oriented, and their focus on the study of objective laws of translation activity. It enables translation scholars to understand peculiarities of various types of translation and to realize the essence of translation as a human activity.